Efficacy and tolerability of VCD chemotherapy in a UK real‐world dataset of elderly transplant‐ineligible newly diagnosed myeloma patients. (5th February 2021) - Rampotas, Alexandros; Djebbari, Faouzi; Panitsas, Fotios; Lees, Charlotte; Tsagkaraki, Ismini; Gomes, Ana Rita; Prideaux, Steve; Chen, Lucia; Prodger, Catherine; Khera, Akhil; Gray, Nicola; Ellis, Lauren; et al.
Abstract: Objective: There are limited data on the efficacy and tolerability of VCD chemotherapy in transplant‐non‐eligible (TNE) newly diagnosed myeloma (NDMM) patients. In this retrospective study, we set out to evaluate this triplet combination in this setting across Thames Valley Cancer Network (UK). Methods: The primary end point was overall response rate (ORR). Secondary outcomes included event‐free survival (EFS), overall survival (OS) and adverse events (AEs). Results: In a total cohort of 158 patients, ORR for total cohort was 72.1%. Median EFS was 10.5 months, and for subgroups by age (<75:11.7 vs ≥75:10.3 months, P  = .124), by Charlson Co‐morbidity Index (CCI) (<5:11.1 vs ≥5:8.2 months, P  = .345). The 4‐month landmark analysis showed the following median EFS results: by cumulative bortezomib dose (≥26 mg/m 2 : 9.0 months vs <26 mg/m 2 : 6.4, P  = .13), by cumulative cyclophosphamide dose (≥7000 mg: 9.2 vs <7000 mg: 7.0 months, P  = .02) and by cumulative dexamethasone dose (>600 mg: 7.8 vs ≤600 mg: 8.3 months, P  = .665). Median OS was 46.9 months. The incidence rate of AE was as follows: any grade (76.8%), ≥G3 (27.1%), ≥G3 haematological AEs (7.9%), any grade infections (31.1%) and ≥G3 infections (11.9%). Conclusion: This study demonstrated a good ORR achieved from fixed duration VCD, which was reasonably well tolerated. This was followed by modest median EFS. We envisage that the latter may be improved in this patient group with the use of a higher cumulative bortezomib dose (≥26 mg/m 2 ) which showed a trend for improved EFS although without statistical significance ( P  = .13), and with the use of a higher cumulative cyclophosphamide doses (≥7000 mg, P  = .02), subject to tolerability and close monitoring.